A Kinetic Study on Starch Digestibility and Polyphenol Release of Different Physically Modified Riceberry Flours during In Vitro Stimulated Gastrointestinal Digestion - Ngô Văn Tài; Naphatrapi Luangsakul (Key engineering materials, 2025)
Riceberry rice has a dark purple color; and a high content of antioxidants, which could affect the digestion behaviors and its application. This study is aimed to analyze the starch digestion rate and predict the bio-accessibility of polyphenols in various modified Riceberry flours during the in vitro digestive process. It also discussed the relationship between the rate of digestion and polyphenol release, which provided basic information about the digestion behavior of Riceberry flour. Seven rice flour samples were used for this study, which included six physically treated flours: annealed flour (AF), heat moisture-treated flour (HMT), pregelatinized flour (Pregel), ultra-sonicated flour (US), wet microwave-treated flour (Wet), dry microwave treated flour (Dry), and untreated (control sample). The obtained results showed that, compared with the control sample, the digestion rate of the Pregel sample was higher, while the others had lower values. However, the Pregel sample showed the second highest rank of bio-accessible polyphenol during digestion after the US sample. While the HMT sample presented the lowest rate of starch digestion and release of bioactive compounds. This investigation also used an artificial neural network (ANN) to forecast the starch digestion and polyphenol bio-accessibility of rice flours. During digestion, the ANN model demonstrated a high capacity to predict the polyphenol bio-accessibility and starch hydrolysis percentage. There was a goodness of fit between the ANN-predicted and the actual values (R 2 >0.95). The importance of the bioavailability and bio-accessibility analysis indicates the functional potential that flour can have, which could be predicted effectively by applying modern techniques such as the ANN model. Moreover, it was also concluded that the digestive tract readily absorbs released polyphenol compounds in rice flour, which also influences the rate of starch hydrolysis. However, the impact could vary depending on the flour’s starch fraction content and the polyphenol activity, which is a topic for future investigation. The high antioxidant content and low digestion rate of flour could be highly promising functional materials for application in the food industry.
Keywords: Food composition and properties; Diet and metabolism studies; Microbial Metabolites in Food Biotechnology